The Association between Exercise Activity and Postural Orthostatic Tachycardia Syndrome (POTS) in Female College Students - Yuliastuti, Afifah Novita; Balgis, .; Kusumawati, Ratna (Nexus Biomedika, 2015)
Background: Postural Orthostatic Tachycardia Syndrome (POTS) is illness manifestations caused by autonomic dysfunction. Subjects with POTS predominantly are young women between 20-40 year old and most of them are college student. Exercise has proven can improve the function of body systems. College studentsâs time is mostly for academic activity and not much time for exercise. The main aim of this research was to know the association between exercise activity andÂ the incidence of POTS in female college students. Method: This research was an analytical observational using case-control design approach. Samples were fifty eight female college students with POTS (16-23 years old) selected using purposive sampling. This study was done from November to December 2014 at Medical School of Sebelas Maret University Surakarta. Data of Exercise activity were obtained by questionnaire. Diagnosis of POTS was conducted by measuring heart rate using pulsemeter on Active Stand Test (AST) position while orthostatic symptoms were gotten by interview. Data were analyzed using Chi-Square test. Result: This study showed that most of the subjects with POTS (27.6%) had lower exercise activity than those without POTS (37.9%). The result of Chi Square analysis was p = 0.007. Conclusion: There was significant association between exercise activity and the incidence of POTS in female college students. Keywords: exercise activity, Â heart rate, POTSÂ